A Hybrid Dynamic/Steady-State Tool With Protection Simulation for Cascading-Outage Analysis of Extreme Events in Power Systems - Bharat Vyakaranam; Nader A. Samaan; Yuri V. Makarov; Tony Nguyen; Yousu Chen; Jeff Dagle; Xiaoyuan Fan; Mallikarjuna R. Vallem; Jose Conto; Sun Wook Kang (IEEE Access)
Large portions of the electrical power grid are susceptible to component failures that when combined with certain other factors (extreme events), could cause cascading outages. Some of these outages can be severe enough to trigger brownouts and blackouts. There are a few established methodologies and tools for directly analyzing the hazards of cascading component outages over a longer time scale although there is a great deal of knowledge regarding the mitigation of the initial few failures that occur near the beginning of a cascade. Current power system tools have limited ability to perform detailed and accurate cascading-outage analysis, which could be computationally intensive. With the help of the Dynamic Contingency Analysis Tool (DCAT), power system planning engineers can evaluate the effects of severe contingencies and possible cascade events on their systems and connections in a more practically grounded manner. DCAT has several unique features: (1) detailed hybrid dynamic and steady-state analysis of power systems to mimic real-world cascading outages, (2) detailed modeling of protection systems embedded in the dynamic simulation, (3) simulation of corrective action after transients, (4) simulation of islanding, and (5) high-performance computing capability to simulate a large number of contingencies in a reasonable time. DCAT outputs will help find technically sound solutions to reduce the risk of cascading outages. This paper provides details of DCAT methodology and shows its capabilities with extreme events on real-world cases.